Using IoT data and applications to improve port-based intermodal supply chains. (January 2020) - Muñuzuri, Jesús; Onieva, Luis; Cortés, Pablo; Guadix, José
Highlights: The availability of real-time information is essential for the efficient management of intermodal chains. IoT systems automate the acquisition and processing of supply chain data. Supply chain transparency is guaranteed for the different stakeholders. Multiple benefits can be expected at the logistic, safety and security, technical and economical levels. The modularity of the system allow for the incorporation of additional services and applications. Abstract: The complexity of port terminal operations and intermodal transshipments has pushed the introduction of information and communication technologies (ICT) to assist the multiple stakeholders involved in the multiple decision-making processes. More recently the development of systems based on the Internet of Things (IoT) represents a further step in the automation of data acquisition and processing. We present here an IoT system designed to optimize, manage and monitor container transport operations along an intermodal corridor, combining rail scheduling and inland vessel navigation. The system has a modular design, enabling the interaction with external systems, independently of their nature, through the cloud-based FIWARE platform. We provide a description of the three inter-related subsystems (container tracking, rail management and inland navigation), and a description of the expected supply chain benefits derived from the implementation of the system, both in terms of shippers and of terminal integration in the logistics flow. This system is currently operative at the Port of Seville, the main transshipment node in the Madrid – Seville – Canary Islands intermodal corridor in Spain.